EFFECT OF TOKAY GECKO (GEKKO GECKO LINNAEUS, 1758) SALIVA ON ANGIOGENESIS DURING WOUND HEALING PHASE OF AUTOTOMIZED TAIL IN COMMON SUN SKINK (EUTROPIS MULTIFASCIATA KUHL, 1820) - Inayah, Nurul; Soesilo, Nyoman Puniawati; Pratiwi, Rarastoeti (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTThe purpose of this study was to investigate the effect of Tokay gecko saliva on morphology and angiogenesis response on the healing process of skink tail wound and also to characterize the protein profile of Gecko saliva. Twelve skinks were autotomized and wound surface of tail smeared by young gecko saliva, adult gecko saliva, and human?s saliva twice per day and control. The morphological changes of the wound surface were observed. The angiogenesis response was observed in vitro using Chorioallantois Membrane (CAM) of the ninth day's chick embryos. Protein profile of gecko saliva analyzed with SDS-PAGE. Generally, treated wound showed a better healing. Young gecko saliva able to stimulate angiogenesis in wound healing stage of sun skink tail after autotomy. Saliva protein of young and adult Gecko differences was not only in the size (or density) but also in the number of the bands. The young and adult Gecko revealed a striking consistency of protein patterns, indicating a profound physiological stability of the whole saliva. This study showed that Gecko saliva able to accelerate wound healing, thus Gecko saliva may have potential me as a future therapeutic for treating infected wounds.Keywords: Tokay gecko saliva, wound healing, sun skink tail, angiogenesis, protein profile.